Identity, Difference and Solidarity: The Challenges and Promises of Articulating Multiple Subjectivities in a Muslim Coalition - Evelyn Hamdon (Adult Education Research Conference, 2007)
Current theorizing about coalitions suggests that the capacity of their members to negotiate multiple and contested identity differences will be important for their survival and efficacy. This qualitative study explored how a Muslim coalition is thinking about and performing identity in the aftermath of September 11th and under the shadow of Islamophobia.